Analysis of Book Distribution Routes Using the Capacity Vehicle Routing Problem (CVRP) Method Using the Sweep Algorithm - Arifta, Ega; Rakhmawati, Fibri (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Distribution is the process of distributing products from producers to consumers. The ease of consumers in obtaining the desired product is the top priority of every company. In the distribution system, the chosen route is the most important element in determining the distance to be traveled and the costs to be incurred. If the chosen route is optimal, then the distribution system becomes more effective and efficient.  Basedon the results of the author's observations, the delivery of goods in the company is still manual and irregular, where the goods are sent from the depot to the consumer and back to the depot so that it takes a lot of time and costs. One solution in solving the distribution problem is the Capacity Vehicle Routing Problem (CVRP).  The Sweep algorithm is the simplest clustering method to solve CVRP. In this study, the author used a sweep algorithm because this algorithm is one of the methods that can solve the problem of the distribution route of Quranic books.  Based onthe results of the study, researchers compared the distribution route usingthe sweep algorithm and the distributionroute of the previous company, obtained a percentage of total mileage savings of 35.35%, namely from the previous total company mileage of 135.2 Km to 87.4 Km by using the Sweep algorithm. This shows that the CVRP method using the sweep algorithm can provide optimal distance and save company expenses.